Challenges and opportunities in upscaling inkjet-printing of OPV - Steinberger, Marc; Qingguang, Xie; Ronsin, Olivier J.J.; Maisch, Philipp; Tam, Kai Cheong; Distler, Andreas; Harting, Jens; Brabec, Christoph; Egelhaaf, Hans-Joachim (Flexible and Printed Electronics, 2024)
The power conversion efficiency and long-term stability of organic solar cells have increased tremendously over the past years, reaching up to 19.2% on research cells and 14.5% on large modules. To take the final step towards industrialization, fabrication methods that can be upscaled and directly implemented in industrial processes need to be developed. In recent years, well-known industrial techniques, like drop-on-demand inkjet printing, have been further developed within the organic photovoltaics (OPV) community, as it enables versatile printing of arbitrary, free-form organic solar modules with different colors-a key feature for modern building-integrated photovoltaics and several niche applications of OPV printed on any kind object. In this review, aside a brief summary of recent developments, we provide an overview of the biggest challenges in OPV inkjet-printing and define design rules to overcome these issues. Further perspectives of OPV inkjet-printing conclude the review.
CRIS-Team Scopus Importer:2025-02-04
Keywords: inkjet-printing; organic photovoltaics; upscaling